Presence of Toxocara spp. Eggs on the houses courtyards soil and feces from pet dogs at Barquisimeto city, Lara state, Venezuela (Gaceta de Ciencias Veterinarias, 2018)
Toxocara spp. are intestinal helminths frequently found in dogs and cats and are capable of causing a parasitic zoonotic disease called toxocariosis. Feces from infected animals represent the main source of environmental contamination and humans can become infected through the accidental ingestion of larval eggs of Toxocara spp. present in soil of public parks, gardens and homes courtyards. These eggs can remain viable in environment for 2 to 4 years or more, being a latent risk factor for human. The research objective was to determine presence of eggs of Toxocara spp. on the houses courtyards and feces of pet dogs of the city of Barquisimeto, Lara State, Venezuela. Samples were taken from soil of previously selected houses courtyards according to established inclusion criteria and analyzed by applying the modified Sloss technique. Feces samples were taken from pet dogs present in these homes and analyzed using the Willis technique. For calculations, frequency and percentage tables were used as well as the association tests: Chi square and Fisher exact test with the statistical package SPSS 15.0 for Windows and 95% was considered as an statistical reliability index (P
Keywords: Toxocara; soil; feces; zoonotic disease; dogs